(untitled) (Educational Dimension, 2020)
Language is not only a structure, but also a place of storage of experience, wisdom, peculiarities of culture, history of the people. Therefore, the question of the functioning and typology of precedent cultural phenomena, for which the storage of the above information is one of the urgent tasks of both linguistics and linguodidactics. The article clarifies the definition of "precedent phenomenon of culture". It is established that the specific features of the precedent phenomena of culture are their speech-communicative essence and national-cultural, socio-cultural or historical-cultural semantic load. It was found that the corpus of precedent phenomena of culture includes such varieties as: phraseology, paremia, names of culturally and historically significant events, objects, proper names, references to well-known artistic and non-artistic texts, linguistic objects, etc. Precedents are those cultural phenomena that are used by native speakers in various communication situations, are understandable to most members of society and are adequately interpreted and evaluated by them. The essential features of the precedent phenomenon of culture are established: metaphorical (figurative, symbolic meaning), labeling, evaluativeness, economy, implicitness, pragmatism, recurrence, historical variability. Classifications of precedent phenomena of culture on various bases are given: on a form of expression, on structural and semantic features, on scale of an audience, on sources of their origin. The functions performed by precedent cultural phenomena in communication are summarized and clarified and which must be taken into account in the process of foreign language learning: nominative, game, password, attraction, image, communicative, allusive, modelling, linguistic-practical, socio-cultural, diagnostic. The level of formation of precedent competence, that is the ability to use precedent cultural phenomena in accordance with the purposes of communication, on the one hand, and on the other – the ability to perceive and understand them according to the communicative intention of the speaker, is an important indicator of secondary language personality.